Економічна та фінансова безпека регіонів в умовах децентралізації - Бурлуцький, Сергій Віталійович; Бурлуцька, Світлана Владиславівна (My University, 2015)
Ціллю роботи є системне узагальнення та обґрунтування науково-методологічних засад економічної та фінансової безпеки регіонів в умовах децентралізації. Зроблено акцент на необхідності системного дослідження співвідношення дефініцій «економічна та фінансова безпека» - «економічна та фінансова безпека регіону». Встановлено, що реалізовані державні заходи з фінансової децентралізації фактично не забезпечують підвищення рівня фінансової безпеки регіонів України.Introduction. The redistributiv mechanisms created in Ukraine don't carry out the leveling function and recreate the existing level of social and economic stratification, worsen the economic and financial security level. Decentralization of the state financial resources and introduction of the budgetary federalism principles will provide protection of regions against negative influences in the financial relations sphere, their financial safety and ability to sustainable development. The aim of work is system generalization and justifications of the scientific and methodological principles of regions economic and financial security in the decentralization conditions. Methods. Basis for research is the dialectic analysis of definitions "economic and financial security", structural decomposition of safety subsystems functions at the regional and local level. The fundamentals for methodology are system approach and a sustainable economic development paradigm. Results. Teoretik-methodological analysis results of the definitions economic and financial security indicate discrepancy of the existing сategorical apparatus to a system paradigm provisions. Decentralization processes of a regional control system and the budgetary decentralization in Ukraine aren't capable to increase the level of financial safety. Conclusion. Institutional reorganization of the relations between the power and business, creation of conditions for effective use of the available regional potential – natural, production, human and financial have to become tackle financial safety problem. It is expedient to use of the communities formation mechanism not only by the territorial principle, and by the tax potential level.
Keywords: системний аналіз; національна безпека; економічна безпека; фінансова безпека; децентралізація; місцеві бюджети; system analysis; national security; economic security; financial safety; decentralization; local budgets; кафедра економіки праці та менеджменту